Geographical influences on the relationship between corporate philanthropy and corporate financial performance - LU, Jane (Institutional Knowledge at Singapore Management University, 2020)
Building on stakeholder theory, the paper argues that geographical differences in stakeholders’ reactions to corporate philanthropy lead to differences in the relationship between corporate philanthropy and corporate financial performance across regions. When comparing the United States and China and different regions within China, it is found that the differences in stakeholder perceptions (as reflected by sinful industry) and information availability (as indicated by advertising intensity) across regions significantly moderate the corporate philanthropy–corporate financial performance relationship. The findings show that the value of corporate philanthropy varies by region and that stakeholder perception and information availability are two important mechanisms through which corporate philanthropy influences corporate financial performance.